Smart environment for smart cities: Assessing urban fabric types and microclimate responses for improved urban living conditions. - (:unkn) unknown (My University, 2014)
The future quality of life within cities is highly dependant on the "smart" treatment of its open space structure. The objective of the present study was to better understand the way in which the small scale structure of the urban fabric contributes differentially to heat island effects and other urban climate phenomena, and to use this information to develop specific strategies for counter-acting and mitigating these effects on a local basis. A major focus has been laid on the urban morphology and in particular the urban landscape, and on understanding its interaction with urban microclimate. The aim was to identify climate sensitive urban patterns - using the example of Vienna - and to suggest concrete open space design measures to counteract the overheating effect during hot summer days. On the basis of a grid used by Statistik Austria (quadrants of 500 m x 500 m) an urban fabric typology for the city of Vienna has been generated taking into account aspects of urban climate and urban structure with regard to terrain, open space and built structure, which influence the microclimatic conditions and parameters. The derived "urban fabric types" have been analysed, characterised, and a sample of the most critical types formed the basis for further investigation of potential open space design measures aimed at counteracting the overheating. This was undertaken using the microclimate simulation programme ENVI-met 4.0. The evaluation of the data generated has focused on thermal comfort and on its most relevant climate factors and has taken the form of maps, mean values and diurnal variations. Based on the evaluation of the simulation results and with regard to results of a previous project, a general catalogue of open space design measures has been compiled. Representative packages of measures have been defined for each sample quadrant, highlighting their specific conditions based on their open space patterns and climate sensitivity, and focused at obtaining the optimal influence on thermal comfort amelioration.
Keywords: Bebauung; Klima; Stadtklima; Mikroklima; Datenerfassung; Stadtstruktur; Bebauung; Freiraum; Bebauungsstruktur; Klimadaten